The Effect of Physical Activity on Blood Pressure in Hypertensive Patients: A Literature Review - Oktaviani Nurhidayah; Fahrun Nur Rosyid (Indonesian Journal of Global Health Research, 2026)
Hypertension has experienced a significant increase in prevalence each year due to unhealthy lifestyles, especially physical inactivity. Good physical activity affects blood pressure in people with hypertension. This study aims to collect and analyze articles discussing the effect of physical activity on blood pressure in people with hypertension. The design used was a literature review. In this study, the author used the Scopus, PubMed, and Science Direct databases to search for articles. The criteria for articles used were those published between 2020 and 2025. The keywords used were physical activity, blood pressure, and hypertension. Based on the eight articles collected, the results showed that physical activity significantly reduced blood pressure in people with hypertension. Overall, the article also shows that physical activity has a positive effect on systolic and diastolic blood pressure. The most significant reduction in blood pressure occurs with moderate to high intensity exercise performed regularly for 6-12 weeks.